Multimedia security and the internet - Zeki, Akram M.; Adamu, Abubakar Ibrahim (IIUM Press, 2015)
The use of data hiding as a viable form of communication has been largely propelled by the growth of the Internet. The Internet offers an opportunity to exchange large amounts of digital information over great distances. The prevalence of media such as audio, videos, and images on the Internet provides an ideal channel for data hiding communication. Voice over Internet Protocol (VoIP) became a natural target for data hiding, it is appropriate to enable hidden communication throughout Internet Protocol (IP) networks. VoIP data hiding covers a wide range of information hiding techniques; including popular techniques based on IP. This chapter is trying to discover some of the data hiding applications and techniques over Internet.